2022
DOI: 10.1590/1807-3107bor-2022.vol36.0038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in the danger zone of mandibular molars after root canal preparation using novel CBCT software

Abstract: Mike Reis BUENO (b) Daniel de Almeida DECURCIO (a) Cyntia Rodrigues Araújo ESTRELA (c) Carlos ESTRELA (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(80 reference statements)
1
2
0
Order By: Relevance
“…This study findings were supported by Kumar et al (27) who concluded TruNatomy exhibited the maximum remaining dentin thickness in comparison to other rotary systems including Neohybrid and ProTaper Next. This study's results were in accordance with Sousa et al (28) Who found that root canals created with files numbered 35 (WaveOne Gold) and 40 (ProTaper Next, BioRace, and Reciproc Blue) left more residual dentin thickness in the distal aspect of the mesial roots of mandibular molars. This indicates that canal preparation in the danger zone can be done safely with these file systems.…”
Section: Discussionsupporting
confidence: 91%
“…This study findings were supported by Kumar et al (27) who concluded TruNatomy exhibited the maximum remaining dentin thickness in comparison to other rotary systems including Neohybrid and ProTaper Next. This study's results were in accordance with Sousa et al (28) Who found that root canals created with files numbered 35 (WaveOne Gold) and 40 (ProTaper Next, BioRace, and Reciproc Blue) left more residual dentin thickness in the distal aspect of the mesial roots of mandibular molars. This indicates that canal preparation in the danger zone can be done safely with these file systems.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, he declared what clinicians had already reported: often, the mesial canals of lower molars don't assume a central position in the root [7]. 'Danger zones' are described as areas where the dentin of the root wall is consistently thin and becomes more fragile and preferred locations for strip perforation during instrumentation [3,8]. Danger zones are commonly seen in mandibular molars [9], maxillary premolars [10], and mesiobuccal roots of maxillary first molars [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) is used as a nondestructive technique for evaluation of the root canal system pre-and post-shaping procedures (6). The remaining dentin thickness in DZ have been assessed in several studies using CBCT (7)(8)(9)(10). In a previous study, in which micro-computed tomographic (µCT) imaging was used as the reference standard, it was showed that dentin thickness can be accurately measured using CBCT imaging after simulated instrument removal (11).…”
mentioning
confidence: 99%